Diagnosing Disease Of Betta Fish Using Fuzzy Logic Sugeno And Forward Chaining Method - Pratama, M Wahyu; Utami, Alvi Syahrini; Kurniati, Rizki (Fakultas Ilmu Komputer Universitas Sriwijaya, 2024)
Betta fish are very popular with people of all ages who make betta fish as small and medium businesses who consider betta fish as a business, but betta fish maintenance is quite the opposite. The ease of breeding betta fish and ignorance in caring for good fish can cause death in betta fish caused by various diseases. Therefore, an expert system for diagnosing disease in betta fish was created. In this study the Forward Chaining method was used to diagnose fish disease, while the Fuzzy Sugeno method determined the severity of the disease. The accuracy generated by the system based on tests carried out using 100 data was 93%.